Effects of genetic ablation and pharmacological inhibition of HuR on gene expression, iron metabolism, and hormone levels - Nathalie Idlin; Sivakumar Krishnamoorthy; Magdalena Wolczyk; Mouad Fakhri; Michal Lechowski; Natalia Stec; Jacek Milek; Pratik Kumar Mandal; Jaroslaw Cendrowski; Christos Spanos; Magdalena Dziembowska; Katarzyna Mleczko-Sanecka; et al. (BMC Biology)
Abstract Background HuR/ELAV1, a ubiquitous RNA-binding protein, belongs to the RNA-binding protein family and is crucial for stabilizing and regulating the translation of various mRNA targets, influencing gene expression. Elevated HuR levels are associated with multiple disorders, including cancer and neurodegenerative diseases. Despite the identification of small molecule inhibitors targeting HuR, their detailed characterization remains limited. Recently, Eltrombopag, an FDA-approved drug for immune thrombocytopenic purpura and chemotherapy-induced thrombocytopenia, emerged as a potential HuR inhibitor. However, the specific molecular pathways influenced by both HuR and Eltrombopag are not fully understood. Results Our study demonstrates that Eltrombopag operates via HuR inhibition, affecting gene expression regulation at the posttranscriptional level. We show that both HuR knockout and Eltrombopag treatment modulate iron metabolism by decreasing ferritin heavy chain (FTH1) and light chain (FTL) synthesis while increasing the expression of iron-regulatory protein 2 (IRP2), a key regulator of ferritin translation. Additionally, HuR inhibition reduces the levels of glycoprotein hormones, alpha polypeptide (CGA), a marker associated with hormone-induced tumors, suggesting a potential use of Eltrombopag in treatment of cancers overexpressing CGA. We observed that the main of control is manifested at the level of translation inhibition, with proteasome-mediated regulation also playing an important role. Conclusions These findings uncover novel posttranscriptional mechanisms governed by HuR and its inhibitor, elucidating pathways relevant to HuR-mediated regulation and molecular therapies aimed at targeting this protein.